The Complete Odes and Satires of Horace - Horace (Book collections on Project MUSE., 1999)
"Horace has long been revered as the supreme lyric poet of the Augustan Age. In his perceptive introduction to this translation of Horace's Odes and Satires, Sidney Alexander engagingly spells out how the poet expresses values and traditions that remain unchanged in the deepest strata of Italian character two thousand years later. Horace shares with Italians of today a distinctive delight in the senses, a fundamental irony, a passion for seizing the moment, and a view of religion as aesthetic experience rather than mystical exaltation - in many ways, as Alexander puts it, Horace is the quintessential Italian. The voice we hear in this graceful and carefully annotated translation is thus one that emerges with clarity and dignity from the heart of an unchanging Latin culture."--Jacket.